OTHR-31. The molecular profile of secondary meningiomas in survivors of childhood non-central nervous system (CNS) cancers. (3rd June 2022) - Corriveau-Bourque, Catherine; Wong, Derek; van Landeghem, Frank; Snuderl, Matija; Spavor, Maria; Yip, Stephen; Eisenstat, David
Abstract: INTRODUCTION: Secondary meningiomas are a late effect in children who received cranial irradiation, frequently with a long latency. The molecular genetic profile of primary meningiomas is well studied; however, few studies describe the genomic landscape of radiation-induced meningiomas (RIM). METHODS: Patients followed at the Stollery Children's Hospital (Edmonton, Canada) with a history of non-CNS malignancies who received cranial irradiation and then developed meningiomas between 1971 and 2013 were identified. Whole exome sequencing (WES), RNA sequencing as well as DNA methylation profiling were performed for patients with available tumor tissue and germline DNA. RESULTS: Of 96 patients who received cranial irradiation for non-CNS tumors, 16 (16.7%) developed symptomatic meningiomas. This patient cohort is unique; all 16 patients identified received 2000-2400 cGy of cranial irradiation, suggesting a threshold dose. 9/16 (56%) had WHO Grade 2 meningiomas or greater and 7/16 (44%) of meningiomas infiltrated other tissues. Post-surgical recurrences occurred in 43%. Patients experienced considerable morbidities directly attributable to the meningiomas or their treatment. 14 patients had samples suitable for further analysis. NF2 mutations were identified in 50% (8; 4 DNA, 4 fusion). Other meningioma related genes with mutations identified in other cohorts were not identified. Copy number alternations were noted in all 16 patients in chromosomes 1p and 22q. 850k methylation analysis with PCA as well as UMAP and tSNE did not demonstrate clustering. Ongoing additional studies include examining tumor mutation burden and the radiation mutational profile. CONCLUSIONS: This study examined the RIM in a cohort of patients having received similar doses of radiation for their childhood cancer. There is increased risk of radiation-induced meningioma in survivors of non-CNS cancers given ≥ 2000 cGy during childhood. To date, our findings are consistent with previously described primary and RIM mutations. Enhanced knowledge in secondary meningiomas is crucial for accurate patient counselling, prognostication, and treatment.